Redundant for Fire Monitoring System Using Raspberry Pi and Arduino Uno - Sazali, Lyana (Journal of Computing Technologies and Creative Content, 2019)
In general, it is hard for them to know whether the temperature inside the house is in a normal or abnormal state. Two LM35 temperature sensors are used to produce a redundancy concept to increase feedback functionality which senses both of the temperature sensors which will be tested inside the room. The values collected are uploaded by Raspberry Pi alternately into the Cloud at regular intervals of time through NodeMCU Wi-Fi module. Thingspeak platform is used, where the user also can see the uploaded values in the graphical term. This project used Arduino Uno, NodeMCU and Raspberry Pi to install all programs that give instructions to conduct this system properly. Lastly, the function of the buzzer sensor in this project is to trigger an alert when the temperature exceeds the desired range to alert the user to check if there is any fire accident occur and take some precautions to avoid the accident from happening.